Three reversible polymorphic copper(I) complexes triggered by ligand conformation: insights into polymorphic crystal habit and luminescent properties - Chai, W.; Hong, M.; Song, L.; Jia, Guohua; Shi, H.; Guo, J.; Shu, K.; Guo, B.; Zhang, Y.; You, W.; Chen, X. (American Chemical Society, 2015)
Three luminescent polymorphs based on a new copper(I) complex Cu(2-QBO)(PPh3)PF6 (1, PPh3 = triphenylphosphine, 2-QBO = 2-(2'-quinolyl)benzoxazole) have been synthesized and characterized by FT-IR, UV-vis, elemental analyses, and single-crystal X-ray diffraction analyses. Each polymorph can reversibly convert from one to another through appropriate procedures. Interestingly, such interconversion can be distinguished by their intrinsic crystal morphologies and colors (namely a, dark yellow plate, ß, orange block, ?, light yellow needle) as well as photoluminescent (PL) properties. X-ray crystal structure analyses of these three polymorphs show three different supramolecular structures from 1D to 3D, which are expected to be responsible for the formation of three different crystal morphologies such as needle, plate, and block. Combination of the experimental data with DFT calculations on these three polymorphs reveals that the polymorphic interconversion is triggered by the conformation isomerization of the 2-QBO ligand and can be successfully controlled by the polarity of the process solvents (affecting the molecular dipole moment) and thermodynamics (affecting the molecular total energy). It is also found that the different crystal colors of polymorphs and their PL properties are derived from different ? values (dihedral angle between benzoxazolyl and quinolyl group of the 2-QBO ligand) and P-Cu-P angles based on TD-DFT calculations. Moreover, an interesting phase interconversion between ? and ß has also been found under different temperature, and this result is consistent with the DFT calculations in which the total energy of ß is larger than that of ?. This polymorphism provides a good model to study the relationship between the structure and the physical properties in luminescent copper(I) complexes as well as some profound insights into their PL properties.